2012
DOI: 10.1148/radiol.11110552
|View full text |Cite
|
Sign up to set email alerts
|

Liver Cancer: Effects, Safety, and Cost-effectiveness of Controlled-Release Oxycodone for Pain Control after TACE

Abstract: CRO is effective, safe, and cost-effective in the control of postoperative pain after transarterial chemoembolization for patients with inoperable liver cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
3
13
0
Order By: Relevance
“…This was consistent with the part result of Ise et al' study (Ise et al, 2009;Wiffen et al, 2014). And other studies showed that there was no abundant evidence to prove which is better ( Fredheim et al, 2010;Zhou et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…This was consistent with the part result of Ise et al' study (Ise et al, 2009;Wiffen et al, 2014). And other studies showed that there was no abundant evidence to prove which is better ( Fredheim et al, 2010;Zhou et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…PCA pumps provide good analgesic effects that alleviate postoperative acute pain; however, they may cause adverse reactions, including respiratory depression, nausea and vomiting, sleepiness, cutaneous pruritus and hepatic dysfunction. 9,10 The results of the present study demonstrated that, compared with a control group, NRS scores in PCA patients gradually decreased over time, confirming the evident analgesic effects of PCA pumps. However, the incidence of postoperative adverse reactions, including nausea and vomiting, cutaneous pruritus, respiratory depression, sleepiness and hepatic dysfunction were significantly higher in PCA patients compared with the control group, indicating the potential risks of using a PCA pump as postoperative analgesic.…”
Section: Discussionsupporting
confidence: 76%
“…23 Studies using PO oxycodone 8,24 after TACE reported an adequate analgesic effect, as defined within these studies. The only available placebo-controlled randomized controlled trial (RCT) 24 reported superior pain control in groups receiving PO controlledrelease oxycodone (CRO). The intervention groups also demonstrated lower pain scores but an increased incidence of mild to moderate RUQP and a shorter LoS.…”
Section: Intravenous or Oral Analgesiamentioning
confidence: 99%
“…The analgesics used were IV morphine 8,15,17 and PO oxycodone 8,24 (PO morphine sulfate was used as a control). 23 Studies using PO oxycodone 8,24 after TACE reported an adequate analgesic effect, as defined within these studies. The only available placebo-controlled randomized controlled trial (RCT) 24 reported superior pain control in groups receiving PO controlledrelease oxycodone (CRO).…”
Section: Intravenous or Oral Analgesiamentioning
confidence: 99%